PENJAMINAN KUALITAS LULUSAN MELALUI PENYELENGGARAAN TUGAS AKHIR PROGRAM - Endang Indrawati; Pepi Rospina Pertiwi (Jurnal Pendidikan Terbuka Dan Jarak Jauh, 2007)
One of the missions of Universitas Terbuka (UT) as a distance education institution is ensuring high academic quality in all aspects of educational management. The ultimate goal is to produce a good quality of graduates for every study program in the institution, this includes Agriculture Extension study program as one of the study program at UT also concerns to produce high quality graduates. Several modifications had been made for delivering a comprehensive examination for Agricultural Extension students in 2005.2.which includes conducting face to face tutorials, providing tutors for assisting students in writing final paper, and conducting assessment evaluation for the written examinations. Comprehensive examination is the ultimate requirements for every students and it is assigned in the end of their study. This article was written based on the portrait of the comprehensive examination mechanism during 2005.2 period. To control the quality Study Program took certain measures which includes by conducting monitoring and evaluating the comprehensive examination in certain regional centres, verification assessment of student final paper submitted by tutor for each regional centre, and conducting assessment evaluation for the written examination by academic staff in the study program using continous ‘running belt’ system